The Influence of Job Demands and Job Resources on Work Engagement Through Job Satisfaction - Pratama, Reza Andhika; Nurlinda, RA (Journal of Current Research In Multidisciplinary, 2025)
The purpose of this study was to investigate the direct effect of job demands and job resources on job satisfaction, to determine the direct effect of job demands and job resources, job satisfaction on work engagement. As well as the indirect effect of job demands and job resources on work engagement through job satisfaction in the production department of PT. Sukses Teknik Inovasi. Data collection was carried out using a questionnaire distributed online using Google from through social media such as Whatsapp. The population in this study were all production employees of the manufacturing company PT. Sukses Teknik Inovasi totaling 400 people. The questionnaires collected were 155 respondents and the data was processed using the SmartPLS analysis tool. From the results of the study, it was found that job demands did not affect job satisfaction. Job resources had a positive effect on job satisfaction. Job demands did not affect work engagement. Job satisfaction had a positive effect on work engagement. Job demands did not affect work engagement through job satisfaction. Furthermore, job resources affected work engagement through job satisfaction. Therefore, it is important for PT. Sukses Teknik Inovasi to reduce high job demands by providing support through job resources, so that employees will feel satisfied in their work and have a positive experience in work engagement.